Increased endothelial expression of Toll-like receptor 2 at sites of disturbed blood flow exacerbates early atherogenic events - Mullick, Adam E. (The Rockefeller University Press, 2008)
Toll-like receptors (TLRs) are pattern recognition receptors of innate immunity. TLRs initiate inflammatory pathways that may exacerbate chronic inflammatory diseases like atherosclerosis. En face laser scanning confocal microscopy (LSCM) of isolated aortic segments revealed the distribution of intimal TLR2 expression and the atheroprotective outcomes resulting from a TLR2 deficiency. TLR2 expression was restricted to endothelial cells in regions of disturbed blood flow, such as the lesser curvature region, in atherosclerosis-prone, low-density lipoprotein receptor–deficient (LDLr (−/−)) mice. Diet-induced hyperlipidemia in LDLr (−/−) mice increased this regional endothelial TLR2 expression. Bone marrow (BM) reconstitution of LDLr (−/−) and LDLr (−/−) TLR2 (−/−) mice created chimeric mice with green fluorescent protein (GFP) expression in BM-derived cells (BMGFP(+)). Lesser curvature BMGFP(+) leukocyte accumulation, lipid accumulation, foam cell generation and endothelial cell injury were all increased by hyperlipidemia, whereas hyperlipidemic double mutant BMGFP(+) LDLr (−/−) TLR2 (−/−) mice had reduced BMGFP(+) leukocyte accumulation, lipid accumulation, foam cells, and endothelial cell injury. This is the first report of in vivo site-specific expression of endothelial cell TLR2. Expression of this receptor on endothelial cells contributed to early atherosclerotic processes in lesion-prone areas of the mouse aorta.